A Rare Complication during Salmonella sp. Infection in a 4-Year-Old Child: Acute Pancreatitis - Kılıç, Ahmet O.; Akın, Fatih; Yazar, Abdullah; Çokbiçer, Abdülkerim; Doğan, Metin; Energin, Vesile M. (Journal of Pediatric Infectious Diseases, 2020)
Objective We aimed to report a rare complication of acute pancreatitis which developed during Salmonella infection.Methods We report a 4-year-old girl with pancreatitis that occurred after salmonella gastroenteritis.Discussion Salmonella sp. infections cause serious mortality and morbidity worldwide. Salmonella transmission is mostly fecal oral from contaminated water and foods. Acute pancreatitis expresses the acute inflammatory process of the pancreas. Inflammation of the pancreas associated with bacterial, viral, and fungal agents can lead to acute pancreatitis. There are limited data regarding the frequency of infections leading to pancreatitis. Here, a pediatric case with pancreatitis that occurred after salmonella gastroenteritis is reported.Conclusion Acute pancreatitis due to S. sp. infection is very rare in children. Pancreatitis should be considered in patients with gastroenteritis with typical abdominal pain.
Keywords: acute pancreatitis; child; complication; poultry; salmonella